Percepción de los hombres adultos frente a los roles sociales que tienen las personas transgénero en el municipio de Samacá (2022)
We currently live in a changing world of constant progress, where society undergoes various transformations that adapt to the demands of everyday life, and how human beings break paradigms and stereotypes that are widely adapted to the social, economic, cultural, and political development of nations.